2019
DOI: 10.2147/cia.s211549
|View full text |Cite
|
Sign up to set email alerts
|

<p>The influence of genetic factors on personality and coping with stress among healthy late reproductive age women</p>

Abstract: Background Psychological stress is a factor which predisposes people to many somatic and mental disorders. Women are at a significantly higher risk of stress than men, and their reactions to stress are stronger. Personality traits are thought to play a special role in the psychology of stress and may be crucial for the choice of a stress-coping strategy. Considering that stress is so common in everyday life, an attempt to understand how stress-coping styles are related to personality and genetic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The currently recognized factors that influence the coping style are attributed to individual factors and external factors. Individual factors refer to age (Stevenson et al, 2012), personal alexithymia (Shen and Xing, 2020), personality (Jurczak et al, 2019), psychological stress (Zhao et al, 2021), etc. External factors include stress (Ryu et al, 2020), social support (Yu et al, 2020), and family environment (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The currently recognized factors that influence the coping style are attributed to individual factors and external factors. Individual factors refer to age (Stevenson et al, 2012), personal alexithymia (Shen and Xing, 2020), personality (Jurczak et al, 2019), psychological stress (Zhao et al, 2021), etc. External factors include stress (Ryu et al, 2020), social support (Yu et al, 2020), and family environment (Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that by the third or fourth month of incarceration, first-time prisoners became assimilated to the regimented and repetitive daily prison routine. Jurczak et al (2019) attempt to understand how stress-coping styles are related to personality and genetic factors acquires special significance. According to the results, all personality traits statistically significantly correlated with the choice of task-oriented coping and emotionoriented coping.…”
mentioning
confidence: 99%